Engineered Probiotics and Pharmabiotics: application in therapeutics and prophylaxis - Patra, Falguni; Duary, Rajkumar; Ganguly, Sangita; Das, Anamika (Indian Journal of Dairy Science, 2017)
Probiotics are defined as â€œlive microorganisms which when administered in adequate amounts confer a health benefit to the hostâ€ (FAO & WHO). Pharmabiotics is a generic term to encompass any form of therapeutic exploitation of the commensal flora, including the use of live probiotic bacteria, probiotic-derived biologically active metabolites, or genetically modified commensal bacteria. Many potentially beneficial probiotics often prove to be physiologically fragile; thereby limiting their clinical applications. Probiotics actions are also not specific in targeting particular pathogens. The concept of genetic engineering seeks to attain this goal, ultimately leading to the development of improved robust probiotic strains for application in therapeutics and prophylaxis. Engineered probiotics and pharmabiotics have been designed to improve storage and delivery in food and other matrices, for improvement of host persistence. Genetic engineering also enabled development of â€˜Designer probioticsâ€™ against enteric pathogens like E. coli, Salmonella, Helicobacter pylori etc., anti-infectives against e.g., HIV, vaginitis, dental caries. Antigens and interleukins are also expressed to combat against IBD / IBS, type I allergy etc. Use of engineered probiotics to deliver therapeutic or prophylactic molecules to the mucosal membrane is recent development in this area. Although there are several advantages, use of designer probiotics raises many questions and concerns as they are GMO. As a phase 1 clinical trial using a genetically engineered Lactococcus lactis has been done for treatment of IBD, engineered probiotics and pharmabiotics appear to be an real alternatives in therapeutics and prophylaxis.